Creoles in education : an appraisal of current programs and projects - Migge, Bettina; Léglise, Isabelle; Bartens, Angela, 1970- (Creole language library, 2010)
This volume offers a first survey of projects from around the world that seek to implement Creole languages in education. In contrast to previous works, this volume takes a holistic approach. Chapters discuss the sociolinguistic, educational and ideological context of projects, policy developments and project implementation, development and evaluation. It compares different kinds of educational activities focusing on Creoles and discusses a list of procedures that are necessary for successfully developing, evaluating and reforming educational activities that aim to integrate Creole languages i.